2019
DOI: 10.1371/journal.pcbi.1007278
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative adaptation to therapy (CAT) confers resistance in heterogeneous non-small cell lung cancer

Abstract: Understanding intrinsic and acquired resistance is crucial to overcoming cancer chemotherapy failure. While it is well-established that intratumor, subclonal genetic and phenotypic heterogeneity significantly contribute to resistance, it is not fully understood how tumor sub-clones interact with each other to withstand therapy pressure. Here, we report a previously unrecognized behavior in heterogeneous tumors: cooperative adaptation to therapy (CAT), in which cancer cells induce co-resistant phenotypes in nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…We found that both competitive and antagonistic interactions increase bulk tumour growth and resistance to radiation. Our results are consistent with findings from previous studies investigating the impact of ecological interactions in chemotherapy: although the type of interaction (e.g., competitive vs. mutualism) can vary, ecological interactions appear to increase resistance to cancer therapy 14 , 17 , 27 29 . Furthermore, in our study, interactions increase the growth and post-radiation survival for the parental population in mixed spheroids in both cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…We found that both competitive and antagonistic interactions increase bulk tumour growth and resistance to radiation. Our results are consistent with findings from previous studies investigating the impact of ecological interactions in chemotherapy: although the type of interaction (e.g., competitive vs. mutualism) can vary, ecological interactions appear to increase resistance to cancer therapy 14 , 17 , 27 29 . Furthermore, in our study, interactions increase the growth and post-radiation survival for the parental population in mixed spheroids in both cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, while reversible drug-tolerant cells may arise naturally in drug-naïve cell populations, their emergence can also be directly influenced by anti-cancer treatment. Further complicating the picture, Craig et al [35] have hypothesized that genotypically and phenotypically distinct cells can cooperate to induce the adoption of drug tolerance, although the potential mechanism behind such cooperation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Full-size  DOI: 10.7717/peerj.10648/ fig-11 immune therapy. One can include a potential interplay between different phenotypes in cancer cells when exposed to therapy (Craig et al, 2019). It would also be interesting to determine the dose effects of various non-cancer cells on both the rate and persistence of tumor growth, and to incorporate not only metabolic interactions but also intercellular crosstalk through growth factors and cytokines, to improve our understanding of the dynamic and highly heterogeneous tumor growth environment.…”
Section: Resultsmentioning
confidence: 99%
“…In future studies, the model presented herein can be amended to include additional cell types found in the tumor microenvironment, such as vascular endothelial cells and immune cells, to understand their role in tumor metabolism and growth and to predict tumor response to therapies such as cytotoxic chemotherapy, metabolic therapy, and immune therapy. One can include a potential interplay between different phenotypes in cancer cells when exposed to therapy ( Craig et al, 2019 ). It would also be interesting to determine the dose effects of various non-cancer cells on both the rate and persistence of tumor growth, and to incorporate not only metabolic interactions but also intercellular crosstalk through growth factors and cytokines, to improve our understanding of the dynamic and highly heterogeneous tumor growth environment.…”
Section: Discussionmentioning
confidence: 99%